Ocular Rosacea Causing Corneal Melt in an African American Patient and a Hispanic Patient - Joanna S. Saade; Bachir Abiad; Jonathan Jan; Dana Saadeh; James P. McCulley; Jeremy Bartley (Case Reports in Ophthalmological Medicine)
Purpose. To discuss two rare presentations of ocular rosacea in a Hispanic patient and an African American patient with unusual ocular manifestations. Case Report. Case  1: a 43-year-old Hispanic woman presented with right eye corneal perforation. Her prior medical history was significant for rosacea only, diagnosed clinically by a dermatologist. Her eye exam showed signs of bilateral ocular rosacea. An emergent full thickness tectonic corneal patch graft was done. The patient’s bilateral eye symptoms improved one month after initiating rosacea treatment. Case  2: a 51-year-old African American man with long standing history of untreated rosacea presented with bilateral peripheral corneal thinning with neovascularization that led to right eye corneal perforation. Glue and bandage contact lens were applied. The patient did well 4 weeks after starting antibacterial, oral steroids, and rosacea treatment. Discussion. Ocular rosacea can present in Hispanic and African American patients with severe manifestations such as corneal perforation.